Eleventh International Conference on Atomic and Molecular Data and Their Applications - Brickhouse, Nancy (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The 11th International Conference on Atomic and Molecular Data and their Applications (ICAMDATA) was held on November 11-15, 2018, in Cambridge, Massachusetts, and was organized by the Center for Astrophysics | Harvard & Smithsonian. This meeting is a continuation of a series which began in 1997 that was chartered to promote the use of atomic and molecular (AM) data in various fields of science and technology, to provide a forum for the interaction of AM data producers and users, and to foster crossdisciplinary cooperation between AM data producers and users as the coordination of AM data activities and databases worldwide.